Spatial-temporal changes assessments of wetlands in port Harcourt city council area of rivers state, Nigeria - M. Menegbo, Emmanuel (International Journal of Engineering and Technology, 2024)
Wetland ecosystems, found in nature, serve as vital habitats for numerous wildlife species and play a crucial role in providing sustenance to both migratory and local animals. Various factors such as climate change, population growth, unemployment, limited market access, inade-quate physical accessibility to wetlands, and lack of knowledge regarding their use contribute to the direct causes of changes in these wet-land areas. Therefore, it becomes crucial to study the spatio-temporal transformation of wetlands to understand the correlation between hu-man activities and wetland evolution. The objective of this study was to determine the distribution and size of wetlands in Port Harcourt city Local Government Area (LGA) in Rivers State, Nigeria. Additionally, the study classifies land cover into different types, identify their pat-terns, and measure the changes that occurred from 2000 to 2020. Land cover change was analysed to understand the specific alterations between the years 2000 and 2020. The Global Land Cover 30 post-processing imageries and Geographic Information System (GIS) tech-niques were employed to capture these changes spanning a 20-year period. By dividing the analysis into two different time periods, it was observed that the wetland area expanded by 1,144,800 square meters from 2000 to 2010. However, between 2010 and 2020, a reduction of 522,900 square meters was observed in the wetland size. Overall, the results demonstrate a net expansion of the wetland area by 621,900 square meters from 2000 to 2020. To ensure sustainable land use, it is crucial to strike a balance between utilization and conservation efforts. Therefore, it is recommended that Nigeria develops and implements policies and laws that effectively address this issue. Moreover, it is imperative to enforce existing policies and laws related to wetland conservation. Furthermore, creating awareness among the population is pivotal in curbing the excessive and inappropriate exploitation of wetlands.